Given "(p^2+q^2)z+px+qy = 0" _______________________(1)
Let "f = (p^2+q^2)z+px+qy"
Using Charpit's Method:
"\\frac{dx}{-\\frac{\\partial f}{\\partial p}} = \\frac{dy}{-\\frac{\\partial f}{\\partial q}} = \\frac{dz}{-p\\frac{\\partial f}{\\partial p}-q\\frac{\\partial f}{\\partial q}} = \\frac{dp}{\\frac{\\partial f}{\\partial x}+p\\frac{\\partial f}{\\partial z}} = \\frac{dq}{\\frac{\\partial f}{\\partial y}+q\\frac{\\partial f}{\\partial z}}"
From last two factor, we get
"\\frac{dp}{p+p(p^2+q^2)} = \\frac{dq}{q+q(p^2+q^2)}" "\\implies \\frac{dp}{p} = \\frac{dq}{q}"
So by integrating, we get "log(p) = log(q) - log(a) \\implies q = ap".
By putting value of "q" in (1), we get
"p^2(1+a^2)z + px+apy = 0 \\\\ \n\\implies p (1+a^2)z + (x+ay) = 0 \\\\\n\\implies p = -\\frac{x+ay}{(1+a^2)z} \\ and \\ q = -\\frac{a(x+ay)}{(1+a^2)z}".
Finally, we have to solve: "dz = pdx+qdy"
"dz = -\\frac{x+ay}{(1+a^2)z} dx -\\frac{a(x+ay)}{(1+a^2)z} dy"
"\\implies (1+a^2)zdz = -xdx - a(ydx+xdy) -a^2 ydy"
So by integrating, we get
"(1+a^2)\\frac{z^2}{2} = -\\frac{x^2}{2} - axy -a^2 \\frac{y^2}{2}"
"\\implies (1+a^2)z^2 = -x^2 - 2axy -a^2 y^2" is the solution of given differential equation.
Comments
Leave a comment